Perbedaan Keluhan Nyeri Punggung Bawah (Low Back Pain) Antara Sikap Kerja Duduk Dan Sikap Kerja Berdiri Di Bagian Produksi Jalur Ii Dan Non Produksi Pt. Wijaya Karya Beton Tbk. Boyolali - Utomo, Arif Budi, Dr. Suwaji, M.Kes, Tarwaka, PGDip Sc, M.Erg (2015)
Low back pain is a common complaint encountered in everyday life. Posture and the posture is one of the risk factors for low back pain. posture categorized into two, standing and sitting. This condition can also be exacerbated by the presence of factors that influence lower back pain such unnatural posture, workload, as well as individual factors (age and body mass index). In part II lane concrete Production workers perform activities such as reinforcement, concrete casting, stretching reinforcement, playback of the mold, and the mold opening stage with a standing working attitude. Worker sitting at work attitude activity reinforcement assembly, mixer operator and machine tools repair. The purpose of this study was to determine whether there are differences in risk levels between standing and sitting work posture against lower back pain. The research method uses an analytic observational study with cross sectional approach. The samples used were 20 workers working attitude stands and 20 workers working attitude sit by sampling using total sampling. Analysis of data using statistical test t-test with a significant level (α = 0.05). Statistical tests using t-test found a significant difference between sitting and standing working attitude towards risk low back pain (p = 0.05). Keywords: Sitting and standing working position, Low Back Pain.